The information in asset fire sales - HUANG, Sheng (Institutional Knowledge at Singapore Management University, 2019)
Asset prices remain depressed for several years following mutual fund ﬁre sales. We show that this price pressure is partly due to asymmetric information which leads to an adverse selection problem for arbitrageurs. After a ﬂow shock, fund managers do not scale down their portfolio, rather, they choose to sell a subset of low-quality stocks that subsequently underperform. In other words, fund managers have stock selling ability. Our ﬁndings suggest an explanation for the tendency of asset prices to remain depressed following ﬁre sales: information asymmetries make it diﬃcult for arbitrageurs to disentangle pure price pressure from negative information.